QseC inhibitors as an antivirulence approach for gram-negative pathogens - Curtis, Meredith M.; Russell, Regan; Moreira, Cristiano G. [UNESP]; Adebesin, Adeniyi M.; Wang, Changguang; Williams, Noelle S.; Taussig, Ron; Stewart, Don; Zimmern, Philippe; Lu, Biao; Prasad, Ravi N.; Zhu, Chen; et al. (American Society for Microbiology, 2014)
Invasive pathogens interface with the host and its resident microbiota through interkingdom signaling. The bacterial receptor QseC, which is a membrane-bound histidine sensor kinase, responds to the host stress hormones epinephrine and norepinephrine and the bacterial signal AI-3, integrating interkingdom signaling at the biochemical level. Importantly, the QseC signaling cascade is exploited by many bacterial pathogens to promote virulence. Here, we translated this basic science information into development of a potent small molecule inhibitor of QseC, LED 209. Extensive structure activity relationship (SAR) studies revealed that LED209 is a potent prodrug that is highly selective for QseC. Its warhead allosterically modifies lysines in QseC, impairing its function and preventing the activation of the virulence program of several Gram-negative pathogens both in vitro and during murine infection. LED209 does not interfere with pathogen growth, possibly leading to a milder evolutionary pressure toward drug resistance. LED209 has desirable pharmacokinetics and does not present toxicity in vitro and in rodents. This is a unique antivirulence approach, with a proven broad-spectrum activity against multiple Gram-negative pathogens that cause mammalian infections.